AES S-box modification uses affine matrices exploration for increased S-box strength - Alamsyah, Alamsyah; Setiawan, Abas; Trisnawan Putra, Anggyi; Budiman, Kholiq; Muslim, Much Aziz; Salahudin, Shahrul Nizam; Prasetiyo, Budi (springer, 2025)
The internet and technological advancements are rapidly growing in this era, potentially giving rise to new challenges, particularly in data security. One algorithm developed to secure data is the Advanced Encryption Standard (AES). The strength of AES lies in its S-box, which transforms input bits into output bits in a randomized manner. Therefore, the S-box must be highly resilient against various attacks, especially linear and differential attacks. This paper modifies the AES S-box algorithm. The modification begins with the irreducible polynomial in the AES S-box, x8 ? x4 ? x3 ? x ? 1. It involves forming an inverse multiplicative matrix, exploring affine matrices, and using an 8-bit constant in the affine transformation. This process produces candidate S-boxes. The candidate S-boxes are subsequently evaluated to ensure they meet the criteria of balance and bijectivity. Once these criteria are satisfied, the candidate S-boxes are formalized into valid S-boxes. The resulting S-boxes are evaluated against several strength criteria, including nonlinearity, strict avalanche criterion, bit independence-nonlinearity criterion, bit independence-strict avalanche criterion, linear approximation probability, and differential approximation probability. The results indicate that the proposed S-box44 has a nonlinearity value of 112, strict avalanche criterion of 0.50073, bit independence-nonlinearity criterion of 112, bit independencestrict avalanche criterion of 0.50237, linear approximation probability of 0.0625, and differential approximation probability of 0.015625. These results outperform the strength of the AES S-box and surpass previous studies.